B. Pascal and S. Frank: A dialogue through the ages - Alyayev , Gennadiy (Sententiae, 2000)
Blaise Pascal and Semen Frank, the author focuses on the affiliation of both thinkers to confessionally atypical Christian movements: Orthodox "Protestantism" (Frank) and Catholic Jansenism (Pascal). The author proves that the key provisions that express the intersections of doctrines of Pascal and Frank are: 1) the notion of philosophy as a kind of revelation based on intellectual intuition rather than rationalistic deductive inferring; 2) the pivotal character of Christological stories for the constitution of anthropology; 3) the antinomic relation between freedom and grace in the understanding of man.